Development of Theoretical Approaches to Modern Document Studies in Linguistic School of Professor Sofiya P. Lopushanskaya - Marina V. Kosova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The article presents fundamental positions of the linguistic school by Sofiya P. Lopushanskaya, Professor of Volgograd State University, and describes their theoretical advancement as being applied in the discourse studies on “Document text: history and modern state”. It explains that the study of business and administrative communication should be based on a clarified definition of the term document as its main constituent. The major goal of documental linguistics is to process a diverse linguistic analysis, discover objective knowledge and reason linguistic comprehension of the documental nature of communication. Within the framework of this review, some general principles of the document text analysis are presented. Firstly, they are statements on: the unity of the speech-making process approach; the interaction and coordination between language phenomena and speech production processes; extralinguistic determination of the modern document. Secondly, these statements were particularized in the linguistic school of Volgograd State University with the aim of introducing basic approaches to the study of the document text. They involve identifying the research object and its characteristics, analyzing a diverse range of texts to assess the genre and style productivity of the document text equally, and defining linguistic categories that are manifested in textual and lingual specificity. The article presents renewed facts on discursive and linguistic features of modern documents united by such text properties as consistency, structure, locality, peculiarities of the language representation of the author and addressee. It is noted that the text of the document can contain information of various qualitative types (factual, conceptual, subtextual), and it is the main constituent of the documental system and the business and administrative communication act. As the text reflects an objective and social reality, its compositional structure and semantic realization greatly depend on extralinguistic constrains. The profiles of the author (addresser) and addressee are presented as being reconstructed with the detailed observation of multi-level lingual and discursive means. The variability of the addressee profiles (the document text addressability) is presented in models of lexical, style, and text adaptation. The principles and methods of detailed description of the documet text specified in the article open up new opportunities and directions for studying document typology and distinguishing relevant features of the document communication.